Auditory Cognitive Function Assessment during Pregnancy : An Event-Related Potential and Neuropsychological Study - Siti Atiyah, Ali; Tahamina, Begum; Faruque, Reza; Wan Rosilawati, Wan Rosli; Wan Nor Azlen, Wan Mohamad (Penerbit USM, 2023)
This monograph provides the readers with a comprehensive neuroscience and cognitive studies in pregnant women in various trimesters of pregnancy. The authors’ goal is to provide significant findings about the states of cognitive function in pregnant women, in response to the claims of the ‘baby brain’phenomenon, which has been debated for years. The event-related potential (ERP) electrophysiological technique is used to capture neural activity at various states of cognitive function, including pre-attentional and attentional processing, during varied types of visual and auditory stimuli. Furthermore, executive function evaluations using various neuropsychological tests are performed as a complement to reveal the states of cognitive function. This monograph provides answers to pregnant women who may experience forgetfulness about what is happening in their brains during pregnancy. It is intended to benefit readers with backgrounds in obstetrics and gyneacology, psychology and cognitive neurosciences. Furthermore, for those who are new to ERP and neuroscience research, this monograph lays out the fundamentals and basics of ERP in an experimental setting.